(untitled) (Altre Modernità, 2019)
For this issue, the Società Italiana delle Letterate presents two contributions: an article by Francesca Maffioli intersecting Amalia Rosselli’s writing with the idea of écriture féminine theorized by Hélène Cixous; and a new review from the future by Sara Positano, who offers an overview of the proceedings from the conference "The space of writing. Compared to female literature" SIL organized in 2002. Both texts represent instances of the critical thought, past and present, that the association keeps producing on women’s literature, in a global perspective. which emerges as topical as ever.